TINDAKAN PASSING OFF DAN PERLINDUNGAN HUKUM TERHADAP PEMILIK MEREK DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Darmiwati; Rahmah, Siti (JURNAL HUKUM DAS SOLLEN, 2023)
ABSTRACT In trade practice, a brand is used as a distinguishing mark between products produced by a person or legal entity and products produced by other parties. Brand reputation influences sales of goods and/or services. On the basis of brand reputation, many consumers are increasingly familiar with the brand. The well-known name of a brand triggers acts of brand infringement. Brand infringement is known as passing. Passing off is categorized as an unlawful act because imitation of a brand is based on bad faith, namely taking advantage of the popularity of another person's brand in such a way that it can harm the brand owner. Product sales may decline if some consumers switch to similar brands. Law Number 20 of 2016 concerning Marks and Geographical Indications with a constitutive or first to file system provides legal protection to parties who register their marks in good faith with the mark registration office, or in this case the Directorate General of Intellectual Property (DJKI) but its implementation has not been effective because there are still registered brands that have the same brand. So it is detrimental to one party.